Spontaneous Transmural Migration of a Retained Surgical Mop into the Small Intestinal Lumen Causing Sub-Acute Intestinal Obstruction: A Case Report - Sarker, Md Moniruzzaman; Kibria, AKM Golam; Haque, Md Manzurul; Sarker, Kali Prosad; Rahman, Md Khalilur (TAJ: Journal of Teachers Association, 2011)
A case of sub-acute intestinal obstruction due to spontaneous complete transmural migration of a retained surgical mop into the small intestinal lumen has been treated surgically in surgery department of Rajshahi Medical College Hospital. The patient presented with colicky abdominal pain, nausea, occasional abdominal distention and vomiting. She had history of abdominal operation twice previously. Abdominal examination revealed a mobile lump in the right side of abdomen. Diagnosis could be made only at laparotomy. doi: 10.3329/taj.v19i1.3167 TAJ 2006; 19(1): 34-37